Cerebellar structural connectivity and contributions to cognition in frontotemporal dementias. (August 2020) - Chen, Yu; Landin-Romero, Ramon; Kumfor, Fiona; Irish, Muireann; Hodges, John R.; Piguet, Olivier
Abstract: Frontotemporal dementia (FTD) is a heterogeneous group of neurodegenerative brain disorders, primarily affecting the frontal and/or temporal lobes. Three main subtypes are recognised, each with distinct clinical and cognitive profiles: behavioural-variant FTD (bvFTD), semantic dementia (SD), and progressive nonfluent aphasia (PNFA). Subtype-specific cerebellar grey matter atrophy has been associated with cognitive dysfunction in FTD; however, the extent and severity of structural abnormalities in the cerebro-cerebellar circuits in these disorders has not been investigated. This study aimed to identify patterns of cerebellar white matter changes and their relations to cognitive deficits in the main FTD subtypes. Results revealed bilateral cerebellar white matter changes in all FTD subtypes compared with controls, with greater cerebellar white matter changes in bvFTD than SD and PNFA. Both afferent and efferent cerebellar pathways were associated with cognition. The profiles of the involvement of cerebellar pathways in cognition varied across FTD syndromes. In bvFTD, the output pathway of the cerebellum was only associated with measures of episodic memory. The input pathway was associated with measures of attention, working memory, visuospatial, episodic memory, executive function, and emotion. In SD, both the output and input pathways were associated with measures of working memory, language, and emotion. Finally, in PNFA, both the output and input pathway of the cerebellum were associated with attention, language, and executive function. Additionally, the input pathway was associated with working memory, visuospatial, and emotion. This study is the first to identify patterns of cerebellar white matter changes across FTD syndromes, which in turn relate to cognitive deficits. These findings extend our understanding of the cerebro-cerebellar networks and provide new insight into the role of cerebellar white matter in cognition.